Uma Abordagem Dirigida por Modelos para Integração de Aplicações Interativas e Serviços Web: Estudo de Caso na Plataforma de TV Digital - Kulesza, Raoni; Meira, Silvio R. L.; Ferreira, Thales P.; Lívio, Álan; Souza Filho, Guido L.; Marques Neto, Manoel C.; Santos, Celso A. S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
This work proposes a model-driven development approach, which integrates interactive multimedia applications, and Web services. It is based on existing modeling language extended, which integrates modeling concepts for interactive applications and ads support for web services. Three Digital TV applications were modeled and developed. As we show, the evaluation of the approach brought benefits not supported by related works, like requirements structuring and reducing amount of work needed to finalize the code generated.